Ayurvedic Management of Kitibhakushta (Guttate Psoriasis) – A Case Report - Sourabh Deshmukh; Trupti Thakre; Pawan R. Naukarkar; Ashvini Pardhekar (Journal of Pharmacy and Bioallied Sciences)
The skin disease in Ayurveda has been classified under Kushta, which is classified as Maha Kushta and Kshudra Kushta. Kitibha Kushta is type of Khudra Kushta. A 26-year-old male patient having brown rough-to-touch hard and dry lesions on a lower limb with itching for 2 years has been treated with Shodhan, followed by Shaman treatment. Shamanchikitsa included Gandhakrasayan and Panchatikta Ghrita after Shodhanchikitsa for 15 days and for local application for 1 month. By using the Ayurvedic modalities, we can find better results in Kushta.